Contribuition for the physical characterization of carolino rice - Correia, Paula (2015)
Most of the rice produced in Portugal is of the Carolino type, botanically classified as Oryza sativa ssp. Japonica. Nowadays, this rice is playing a vital role in Portuguese rice trading, and therefore the aim of this work was to evaluate some cultivars as to biometric characteristics, water uptake ratio, cooking time and textural properties. Five types of Carolino rice were collected for analysis. Biometric characteristics (length, width, length/width ratio) were evaluated using an automatic biometric equipment. Other morphological characteristics were evaluated: white vitreous, total whiteness, vitreous percentage, percentage of chalky area and kett (using a colorimeter). Texture was evaluated on compression by texture profile analysis with a texturometer. The samples studied showed biometric characteristics to be commercially classified as long grains type-A. The results indicated that one of the samples was quite different from the others, presenting less adhesiveness, and lower hardness, springiness and cohesiveness. Also some differences were found between different rice samples regarding colour characteristics, cooking time and water absorption.